2019
DOI: 10.1073/pnas.1900801116
|View full text |Cite|
|
Sign up to set email alerts
|

Childhood trauma history is linked to abnormal brain connectivity in major depression

Abstract: Patients with major depressive disorder (MDD) present with heterogeneous symptom profiles, while neurobiological mechanisms are still largely unknown. Brain network studies consistently report disruptions of resting-state networks (RSNs) in patients with MDD, including hypoconnectivity in the frontoparietal network (FPN), hyperconnectivity in the default mode network (DMN), and increased connection between the DMN and FPN. Using a large, multisite fMRI dataset (n= 189 patients with MDD,n= 39 controls), we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(138 citation statements)
references
References 79 publications
10
127
1
Order By: Relevance
“…Stress experienced early in life can change circuit development and response to later stress and reward, which are likely mediated in part by transcriptional changes in the brain early in life and sustained across the lifespan 7,[19][20][21][22] . Here, we present systematic mapping of enduring ELS-induced transcriptomic changes in three reward-associated brain regions key to depression-like behaviors 23 , in both male and female mice, and we further assess transcriptomic responses to a second stress in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Stress experienced early in life can change circuit development and response to later stress and reward, which are likely mediated in part by transcriptional changes in the brain early in life and sustained across the lifespan 7,[19][20][21][22] . Here, we present systematic mapping of enduring ELS-induced transcriptomic changes in three reward-associated brain regions key to depression-like behaviors 23 , in both male and female mice, and we further assess transcriptomic responses to a second stress in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we reveal new brain regions connected to these well‐established regions. Further, we identify nodes in the DMN, executive control network, and SAL network that are well described in previous studies (Sheline et al, ; Sheline, Price, Yan, & Mintun, ; Yu et al, ). Our results also highlight new findings on hub regions in the association cortex that link to these established networks.…”
Section: Resultsmentioning
confidence: 89%
“…We compared the performance of MSNR to two of the most commonly used single-scale network regression analyses, namely the individual edge model (Grillon et al 2013;Lewis et al 2009) and the community mean model (Yu et al 2019;Betzel et al 2014;King et al 2018;Yan et al 2019). These two approaches have been commonly used to study connectivity-phenotype relationships (Craddock, Tungaraza, and Milham 2015;Varoquaux and Craddock 2013) and differ primarily in the scale at which the brain network is examined ( Fig.3).…”
Section: Comparison To Single-scale Approachesmentioning
confidence: 99%
“…A community refers to a collection of nodes that are highly connected to each other and have little connection to nodes outside of the community. Prior work has demonstrated that brain network architecture present on these different scales is associated with development and aging (Power et al 2010;Gu et al 2015;Betzel et al 2014), cognition (Crossley et al 2013;Park and Friston 2013;Bressler and Menon 2010), and neuropsychiatric diseases (Yu et al 2019;Braun et al 2016;Fornito, Zalesky, and Breakspear 2015;Grillon et al 2013;Bassett, Xia, and Satterthwaite 2018;Xia et al 2018;Kernbach et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation